2021
DOI: 10.1088/1674-1056/ac0db3
|View full text |Cite
|
Sign up to set email alerts
|

Photonic-plasmonic hybrid microcavities: Physics and applications*

Abstract: Photonic-plasmonic hybrid microcavities, which possess a higher figure of merit Q/V (the ratio of quality factor to mode volume) than that of pure photonic microcavities or pure plasmonic nano-antennas, play key roles in enhancing light–matter interaction. In this review, we summarize the typical photonic-plasmonic hybrid microcavities, such as photonic crystal microcavities combined with plasmonic nano-antenna, whispering gallery mode microcavities combined with plasmonic nano-antenna, and Fabry–Perot microca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 140 publications
0
10
0
Order By: Relevance
“…The frequency and strength of absorption depends on the geometry of resonator and substrate thickness. Various MTM absorbers of different spectral range are realized with reference to above design [29][30][31][32][33][34][35][36][37][38][39]. In 2009, an MTM absorber with dendritic (branched form) unit cells was reported.…”
Section: Narrowband Mtm Absorbersmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency and strength of absorption depends on the geometry of resonator and substrate thickness. Various MTM absorbers of different spectral range are realized with reference to above design [29][30][31][32][33][34][35][36][37][38][39]. In 2009, an MTM absorber with dendritic (branched form) unit cells was reported.…”
Section: Narrowband Mtm Absorbersmentioning
confidence: 99%
“…At the same time, it is to be noted that applications related to energy harvesting, scattering reduction and thermal sensing require absorption [25][26][27]. It is reported that tailoring of magnetic and electric resonances lead to usage of above mentioned inherent loss in achieving MTM's of uniform absorption [28][29][30][31][32][33][34]. Perfect absorber with metamaterial reported for the first time exhbited narrow bandwidth assigned to resonance condition limiting its usage for practical applications [28].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, optical μCVs comprise two mirrors arranged in parallel at each end of a “defect” region (i.e., a cavity), the function of which is to increase the effective optical path through spatial and temporal confinement of light within the defect feature. , The capability of μCVs to confine light is defined by a figure of merit known as the quality factor, which represents the spectral energy density of the confined light within the structure. The strength of light confinement is characterized by a narrow and well-resolved resonance band (RB) in the optical spectrum of the PC structure. , Light confined within μCVs is susceptible to altering their properties when the localized refractive index of the structure is modified. The spectral properties of the characteristic RB, including its line width and frequency, undergo shifts in response to slight variations in the environment of the optical μCV system.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of light confinement is characterized by a narrow and well-resolved resonance band (RB) in the optical spectrum of the PC structure. 27,28 Light confined within μCVs is susceptible to altering their properties when the localized refractive index of the structure is modified. The spectral properties of the characteristic RB, including its line width and frequency, undergo shifts in response to slight variations in the environment of the optical μCV system.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hybrid photonic-plasmonic devices have also been demonstrated to offer unique opportunities for various applications as they provide ideal platforms for enhancing light-matter interaction [29,30]. For instance, an optical refractive index sensor based on a photonic crystal structure integrated with metallic nanorods was shown to outperform the pure plasmonic or photonic crystal sensors as the localized surface plasmons increase the interaction of the optical field and the matter inside the cavity.…”
Section: Introductionmentioning
confidence: 99%